The 1522 Siege of Rhodes
1 online resource.
Keywords: "In 1522 the Ottomans attacked the island of Rhodes and, after a six-month siege, the Hospitallers surrendered on terms. The Knights Hospitaller had ruled Rhodes since 1309 and the Ottomans had attempted to capture the island forty years before in 1480, but were defeated by the Knights. The Ottoman victory in 1522 resulted in the Knights being expelled from the island and eventually settling in Malta, Gozo, and Tripoli, and the Ottomans obtaining domination over the Eastern Mediterranean and its trade. This collection of essays, published on the 500th anniversary of the siege, explores such question as why Suleiman the Magnificent attacked Rhodes, what made the 1522 siege successful, and how the Rhodian population, the Knights Hospitaller, the Eastern and Western Mediterranean and Europe in general were affected by the loss of Rhodes. The answers to these questions are explored in new research by expert historians and archaeologists in their field. This book will appeal to all those interested in the Knights Hospitaller, Ottoman History, Crusader Studies, and Early Modern European History"--